Forage sorghum production under rainfed farming in sites with and without climate restriction for maize cultivation - Farias, Paulo Cesar Batista de; Bezerra, Leilson Rocha; Silva, Alex Lopes da; Nascimento, Romilda Rodrigues do; Azevedo, Felipe Luênio de; Ezequiel, Francigefeson Linhares dos Santos; Araújo, Marcos Jácome de; Edvan, Ricardo Loiola (Semina: Ciências Agrárias, 2022)
Forage sorghum is a crop that can be planted in semiarid regions, due to its greater adaptability to dry climate environments, and can replace maize in these regions, which are often unsuitable for its production. Thus, the objective of the study was to evaluate the structural, morphological and nutritional characteristics of 23 sorghum hybrids forage cultivated in rainfed conditions, planted in different climate conditions, comparing the hybrids, in order to determine what produces the best in the climatic conditions of the explored region, and also to indicate whether this crop can be planted as a replacement for maize in environments not suitable for planting it. The research was conducted in climate BSh in the Municipality of Alvorada do Gurgueia, and climate Aw in the Municipality of Bom Jesus, both in the state of Piauí from 2014 to 2015. Each trial consisted of 20 experimental forage sorghum hybrids [Sorghum bicolor (L.) Moench], and three commercial hybrids. A randomized block design was used, with three replications in a factorial scheme (2 Ã— 23). The growth characteristics determined were hybrid Ã— climate interaction for the variables plant height, lodging and leaf/stem ratio. For the variable number of tillers, there was a significant difference only between hybrids. There was no difference between hybrids only for the lodging variable of climate Aw. The other variables showed a difference in all hybrids evaluated. There was an interaction for production of dead matter and total dry forage mass between the different environments and hybrids evaluated. For leaf production, there was an effect only for the different environments. For the chemical characteristics, there was an interaction for all variables analyzed between the different environments and hybrids evaluated. The semi-arid region of the State of Piauí, climate BSh which presents a high climatic risk for maize cultivation, proved to be favorable for forage sorghum production. The forage sorghum also presented agronomic characteristics similar to those found in semi humid climate Aw, a favorable region for maize cultivation. In addition, the tested hybrids showed good chemical characteristics, so the BSh climate has great exploratory potential for the cultivation of forage sorghum.